2011
DOI: 10.1167/11.14.6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired visual decision-making in individuals with amblyopia

Abstract: This study examined the effects of amblyopia on perceptual decision-making processes to determine the consequences of visual deprivation on development of higher-level cortical networks outside of visual cortex. A variant of the Eriksen flanker task was used to measure response time and accuracy for decisions made in the presence of response-selection conflict. Performance of adults with amblyopia was compared to that of neurotypical participants of the same age. Additionally, simple and choice reaction time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 46 publications
5
49
0
1
Order By: Relevance
“…They found that amblyopes significantly underestimated the number of targets when using their amblyopic eye compared to the nonamblyopic eye and controls across all cueing conditions, which they argue to be evidence for a “high-level deficit.” Note that even though their amblyopes do exhibit a robust and reliable endogenous attention effect (valid vs. invalid cueing) of the same magnitude as that shown by visually intact observers, this study is often cited as one of the primary studies providing evidence for a visual attention deficit in amblyopia (Farzin & Norcia, 2011; Ho et al, 2006; Hou et al, 2016; Levi, 2013; Levi & Tripathy, 2006; McKee, Levi, Schor, & Movshon, 2016; Secen et al, 2011; Tripathy & Levi, 2008). …”
Section: Introductionmentioning
confidence: 74%
“…They found that amblyopes significantly underestimated the number of targets when using their amblyopic eye compared to the nonamblyopic eye and controls across all cueing conditions, which they argue to be evidence for a “high-level deficit.” Note that even though their amblyopes do exhibit a robust and reliable endogenous attention effect (valid vs. invalid cueing) of the same magnitude as that shown by visually intact observers, this study is often cited as one of the primary studies providing evidence for a visual attention deficit in amblyopia (Farzin & Norcia, 2011; Ho et al, 2006; Hou et al, 2016; Levi, 2013; Levi & Tripathy, 2006; McKee, Levi, Schor, & Movshon, 2016; Secen et al, 2011; Tripathy & Levi, 2008). …”
Section: Introductionmentioning
confidence: 74%
“…Because the amblyopic eye does not determine the saccadic target, it probably has little influence on selective attention during binocular viewing, and may suffer from inadequate command of attention even during monocular viewing. Several studies have found abnormalities in the control of attention by the amblyopic eye (Farzin & Norcia, 2011; Kiorpes, Pham, & Carrasco, 2012; Popple & Levi, 2008; Sharma, Levi, & Klein, 2000). Lai, McKee, Hou, and Verghese (2013) found that the amblyopic eye could use cued attention to enhance contrast sensitivity, but that the shift in attention to the cued site was delayed, compared to normal observers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that the amblyopic deficit is then amplified downstream (Levi, 2006; Muckli et al, 2006). Thus amblyopes suffer not only from sensory deficits, but also from deficits not simply explained by low-level considerations (Farzin & Norcia, 2011; Kiorpes, 2006; Levi, 2006; Sharma, Levi, & Klein, 2000). These include second-order processing, contour integration, and temporal, spatial and/or capacity limits of attention.…”
Section: Introductionmentioning
confidence: 99%